Perbedaan Konsentrasi Ragi terhadap Kualitas Donat Mochi - Diece Harti Subargah; Kirey Qanita Renada; Naneu Nurfarida Kurniawan; Peristiwati (Program Studi Teknologi Hasil Pertanian, 2025)
Mochi donuts are an innovative bakery product that combines the traditional shape of donuts with the chewy texture of mochi. Fermentation plays a key role in shaping their final quality, with yeast concentration being one of the most critical factors. This study aims to determine the optimal yeast concentration that produces mochi donuts with the best sensory characteristics. The research employed a completely randomized design experimental method with three treatments: yeast concentrations of 1.3%, 1.5%, and 1.7%. Seventeen randomly selected panelists evaluated the aroma, taste, and texture of the donut samples using organoleptic tests. The results show that the 1.5% yeast concentration produced mochi donuts with the most desirable characteristics. This sample received the highest preference due to its balanced fermentation aroma, soft and consistent texture, and mild acidity. In contrast, the 1.3% concentration resulted in excessive acidity and unstable texture due to under-fermentation, while the 1.7% concentration led to over-fermentation, negatively affecting aroma and texture. These findings highlight that a precise balance in yeast concentration is essential to optimize sensory quality. Future research is encouraged to explore other influencing factors such as fermentation duration, temperature, or different yeast strains to further enhance the nutritional value, stability, and market potential of mochi donut products.